Cognitive Structures of Space-Time - Signorelli, Camilo Miguel; Dündar-Coecke, Selma; Wang, Vincent; Coecke, Bob (Frontiers in Psychology, 2020)
Causation refers to relation, while space-time constitutes an abstract schema for causal connections between events, objects, and processes. Moreover, the mental representations of such events and relations seem to afford compositionality. Considering these notions, we posit an interplay between the physical structural properties of space-time and the compositional and operational modalities upon object and relational representations available to the reasoner therein. This hypothetical relation is defined and discussed. For instance, a “topological-temporal” schema, motivated by causal considerations from narrative information, might license talk of temporal precedence, succedence, and concurrency between some events, but not necessarily the duration of events, which requires an augmented “metric-topological” temporal schema to speak of the temporal distance between points in time. Therefore, our proposed model emphasizes that hierarchies of structural properties of certain space-time schema are important to explore, together with attendant considerations on the levels of complexity of settling causal queries within them. This discussion motivates advanced contributions to the psychological, physical, and philosophical discourse on causal cognition.